2023
DOI: 10.3847/1538-4357/acb340
|View full text |Cite
|
Sign up to set email alerts
|

Black Hole Ultracompact X-Ray Binaries: Galactic Low-frequency Gravitational Wave Sources

Abstract: In the Galaxy, close binaries with compact objects are important low-frequency gravitational wave (GW) sources. As potential low-frequency GW sources, neutron star/white dwarf (WD) ultracompact X-ray binaries (UCXBs) have been investigated extensively. Using the Modules for Experiments in Stellar Astrophysics code, we systematically explored the evolution of black hole (BH)-main-sequence star (MS) binaries to determine whether their descendants can be detected by space-borne GW detectors. Our simulations showe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 143 publications
1
15
1
Order By: Relevance
“…Chen et al (2020) estimated that the main-sequence (MS) channel can form 60-80 NS UCXB-LISA sources in the Galaxy. However, LISA can only detect ∼4 BH UCXBs evolving from the MS channel (Qin et al 2023). If the ratio of the numbers between NS and BH UCXB-LISA sources is similar to that of the identified numbers between NS and BH UCXBs, the number of confirmed BH UCXBs evolving from the MS channel is ∼1, which is comparable to the present observation.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Chen et al (2020) estimated that the main-sequence (MS) channel can form 60-80 NS UCXB-LISA sources in the Galaxy. However, LISA can only detect ∼4 BH UCXBs evolving from the MS channel (Qin et al 2023). If the ratio of the numbers between NS and BH UCXB-LISA sources is similar to that of the identified numbers between NS and BH UCXBs, the number of confirmed BH UCXBs evolving from the MS channel is ∼1, which is comparable to the present observation.…”
Section: Introductionsupporting
confidence: 84%
“…If the MS star starts mass transfer late enough and the orbital-angularmomentum loss by magnetic braking is efficient, the system would evolve toward a UCXB. In this channel, UCXBs generally evolve from BH/NS+MS binaries whose initial orbital periods are shorter than the bifurcation period (van der Sluys et al 2005;Sengar et al 2017;Chen et al 2020;Qin et al 2023). In the UCXB stage, the donor star is most likely to evolve into a WD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, UCXBs with an NS/BH accretor have been suggested to be a product of binary star evolution in one of the following three scenarios (depending on the nature of the companion star): (i) a WD companion that loses orbital angular momentum because of GW radiation, leading to the onset of mass transfer as mentioned above (Pringle & Webbink 1975;Yungelson et al 2002;Sengar et al 2017;Qin et al 2023); (ii) a helium star donor filling its Roche lobe (Savonije et al 1986;Yungelson 2008;Wang et al 2021); and finally, (iii) a binary consisting of a low-mass main-sequence (MS) star that initiates mass transfer when the donor star is near the end of hydrogen core burning, thereby being stripped to a naked He-rich core (Nelson et al 1986;Podsiadlowski et al 2002). If companions to BH-UCXBs turn out to be He WDs, or naked He-rich cores evolved from stripped low-mass MS stars, their formation path is likely to follow that of NS-UCXBs with similar donors-a scenario that despite common acceptance still challenges our current understanding of how magnetic braking operates to keep the orbit tight with the removal of orbital angular momentum (Chen et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For inspiral DCOs in the Milky Way, it is expected that they can spend a typical duration of ∼10 6 yr in the LISA band. Previous studies of binary population synthesis (BPS) have shown that LISA can identify a large number of resolved DCOs in the Milky Way (see Amaro-Seoane et al 2023, for a review), including thousands of double white dwarf (WDWD) systems (e.g., Nelemans et al 2001;Liu et al 2010;Ruiter et al 2010;Korol et al 2017;Lamberts et al 2019;Breivik et al 2020), hundreds of NSWD systems (e.g., Tauris 2018;Chen et al 2020Chen et al , 2021Wang et al 2021), and tens of other types of DCO systems with BH and/or NS components (e.g., Belczynski et al 2010a;Liu & Zhang 2014;Lamberts et al 2018;Andrews et al 2020;Lau et al 2020;Sesana et al 2020;Shao & Li 2021;Wagg et al 2022b;Gao et al 2022;Feng et al 2023;Qin et al 2023). Outside the Milky Way, it is predicted that a number of DCO systems in the Local Group galaxies are detectable by LISA (Korol et al 2018;Seto 2019;Andrews et al 2020;Lau et al 2020).…”
Section: Introductionmentioning
confidence: 99%